Revealing the solid-solution interface interference behaviors between Cu²⁺ and As(III) via partial peak area analysis of simulations and experiments - Liang, Bo (2023)
The mutual interference in the sensing detection of heavy metal ions (HMIs) is considerably serious and complex. Besides, the co-existed ions may change the stripping peak intensity, shape and position of the target ion, which partly makes peak current analysis inaccurate. Herein, a promising approach of partial peak area analysis was proposed firstly to research the mutual interference. The interference between two species on their electrodeposition processes was investigated by simulating different kinetics parameters, including surface coverage, electro-adsorption, -desorption rate constant, etc. It was proved that the partial peak area is sensitive and regular to these interference kinetics parameters, which is favorable for distinctly identifying different interferences. Moreover, the applicability of the partial peak area analysis was verified on the experiments of Cu2+, As(III) interference at four sensing interfaces: glassy carbon electrode, gold electrode, Co3O4, and Fe2O3 nanoparticles modified electrodes. The interference behaviors between Cu2+ and As(III) relying on solid-solution interfaces were revealed and confirmed by physicochemical characterizations and kinetics simulations. This work proposes a new descriptor (partial peak area) to recognize the interference mechanism and provides a meaningful guidance for accurate detection of HMIs in actual water environment.